DEVELOPMENT OF ANIMATION-BASED MATHEMATICS LEARNING MEDIA USING CANVA TO ENHANCE CONCEPTUAL UNDERSTANDING - Siregar, Pariang Sonang; Hasrijal, Hasrijal; Hatika, Rindi Genesa (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Mathematics is often perceived as abstract and difficult, limiting students’ conceptual understanding and engagement. To address this challenge, this study aims to develop animation-based mathematics learning media using Canva to enhance students' conceptual understanding. Employing a research and development (R&D) methodology, the study adopts the 4D model (Define, Design, Develop, and Disseminate). The media was designed to support interactive and visual learning experiences in mathematics, specifically targeting the improvement of students’ grasp of abstract mathematical concepts. Validation was conducted by a panel of experts, including content experts, media design experts, and instructional experts. The results showed a content validity score of 92.5%, indicating that the media is highly valid in terms of content relevance, accuracy, and alignment with curriculum standards. The practicality of the media was evaluated through teacher and student responses, yielding a practicality score of 89.2%, suggesting that the media is easy to use, engaging, and effective in classroom settings. These findings demonstrate that the Canva-based animation media is both valid and practical for use in mathematics instruction. It is recommended for broader implementation to improve conceptual understanding and learner engagement in mathematics education.